2021
DOI: 10.3345/cep.2020.01039
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of Toxocara spp. in pediatrics: a systematic review and meta-analysis

Abstract: Background Toxocariasis is a zoonotic parasitic disease caused by Toxocara canis and Toxocara cati in humans. Various types of T. canis are important. Purpose The current study aimed to investigate the prevalence of Toxocara spp. in pediatrics in the context of a systematic review and meta-analysis. Methods The MEDLINE (PubMed), Web of Sciences, Embase, Google Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…A recent meta-analysis study has shown that frequency of anti- Toxocara antibodies in pediatric population worldwide was approximately 30% (IC = 22–37%: I 2 = 99.11%; p < 0.05), similarly to the present study of 31.8% prevalence in under-18 individuals ( 26 ). Despite another up-to-date survey has also found youth as likely risk factor for toxocariasis (OR = 1.89; IC = 1.72–12.8), authors have not assessed presence of dog and cat contact as associated risk factor for youngers ( 4 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A recent meta-analysis study has shown that frequency of anti- Toxocara antibodies in pediatric population worldwide was approximately 30% (IC = 22–37%: I 2 = 99.11%; p < 0.05), similarly to the present study of 31.8% prevalence in under-18 individuals ( 26 ). Despite another up-to-date survey has also found youth as likely risk factor for toxocariasis (OR = 1.89; IC = 1.72–12.8), authors have not assessed presence of dog and cat contact as associated risk factor for youngers ( 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Assessment of potential associated risk factor related to seroprevalence of anti- Toxocara (IgG) antibodies and contact with dogs and cats was made by evaluation of odds ratio (OR) and Confidence Interval (CI) of 95%. Forest plots were constructed to present results of meta-analysis in a schematic fashion and with funnel graphics (each study was represented by a proportional effect size), and it was performed to assess publication bias ( 26 , 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…A high distribution of toxocariasis is observed in both industrial and developing countries [ 7 ]. The seroepidemiology of toxocariasis in different geographic regions is diverse, which has been reported from 3% to 79% globally with an upstream in Asian countries [ 8 ]. In a study, 22.3% of suspected people in Bulgaria were Toxocara seropositive [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with low levels of education, living in poverty, or in areas with a lower Human Development Index (a composite measure of life expectancy, education and national income), poor sanitation and hygiene 8 18–20…”
Section: Risk Factors For Infectionmentioning
confidence: 99%